Phytochemical analysis in foamy extract of cucumber (Cucumis sativus L.): Phytochemical analysis in foamy extract of cucumber - Kumaraswamy, Latha (SAARC Journal of Agriculture, 2022)
The metabolite profiling of white foamy substance local white cultivar of Cucumber (Cucumis sativus L.) was performed using HR-LCMS. Prominent compounds with MS spectra, peak list, and compound structure were studied. Which pertains to Cucurbitaceae. The cytotoxic activity was studied on onion root tip squash and microscopic evaluation was done. The principal component analysis (PCA) of the analytical data showed the presence of Triterpenes: Cucurbitacin-C (0.8ppm), Cucurbitacin-E (5.53ppm) and Cardiac glycosides: Gitoxigenin (7.76ppm), Strophanthidin (13.79ppm), and Digitoxigenin (2.13ppm) in 10μl of the loaded sample.100 other compounds were identified by accurate mass of Q-TOF/MS and verified by database compounds (IRM calibration). Strophanthidin in the highest concentration in the foamy extract is a significant finding. This study reports the traditional significance of removing white foamy substances for bitterness in cucumber before slicing. The cytotoxic study on onion root tips by photomicrograph study indicates reduction in root growth and chromosomal aberrations, disturbed telophase, anaphase, abnormal cell shape, dissolved chromosomes, membrane damage and nuclear lesions. SAARC J. Agric., 20(2): 145-155 (2022)